Diagnosis and treatment of patients with antiphospholipid syndrome: a mixed-method evaluation of care in The Netherlands. Issue 2 (12th June 2020) - Klein Haneveld, Mirthe J; Lemmen, Caro H C; Brunekreef, Tammo E; Bijl, Marc; Jansen, A J Gerard; de Leeuw, Karina; Spierings, Julia; Limper, Maarten; ,
Abstract: Objectives: The aims were to gain insight into the care provided to patients with APS in The Netherlands and to identify areas for improvement from the perspective of both patients and medical specialists. Methods: APS care was evaluated using qualitative and quantitative methods. Perspectives on APS care were explored using semi-structured interviews with medical specialists, patient focus groups and a cross-sectional, online patient survey. In order to assess current practice, medical records were reviewed retrospectively to collect data on clinical and laboratory manifestations and pharmacological treatment in six Dutch hospitals. Results: Fourteen medical specialists were interviewed, 14 patients participated in the focus groups and 79 patients completed the survey. Medical records of 237 patients were reviewed. Medical record review showed that only one-third of patients were diagnosed with APS within 3 months after entering specialist care. The diagnostic approach and management varied between centres and specialists. Almost 10% of all patients and 7% of triple-positive patients with thrombotic APS were not receiving any anticoagulant treatment at the time of medical record review. Correspondingly, poor recognition and fragmentation of care were reported as the main problems by medical specialists. Additionally, patients reported the lack of accessible, reliable patient education, psychosocial support and trust in physicians as important points for improvement. Conclusion: Delayed diagnosis, variability in management strategies and fragmentation of care were important limitations of APS care identified in this study. A remarkable 10% of patients did not receive any anticoagulant treatment.